Active du/dt Filtering for Three Phase Motor Drive Applications - Kohlhepp, Benedikt; Ye, Tianlun; Dürbaum, Thomas (ICPE 2023-ECCE Asia - 11th International Conference on Power Electronics - ECCE Asia: Green World with Power Electronics, 2023)
The performance of modern wide bandgap semiconductors cannot be fully exploited in inverters for motor drive applications, since faster switching is not possible due to the high du/dt causing overvoltages due to reflections on cables and EMI issues. Classical LC filters are also not suitable, as these limit power density. This situation calls for an active du/dt filter implementing intelligent switching transitions of the power semiconductors to ensure high efficiency and low du/dt at the output simultaneously. Theoretically, the modulation scheme can deliver ideal smooth transitions. However, in practical setups non-idealities cause severe oscillations of the resonant tank. This paper studies the origin of this oscillation and proposes a compensation method to successfully reduce the undesired oscillation.
CRIS-Team Scopus Importer:2023-09-22
Keywords: Active du/dt filter; GaN; Inverter; Nonidealities